Factors influencing decision-making role preferences: a qualitative study of Malaysian patients with type 2 diabetes during insulin initiation - Lee, Yew Kong; Low, Wah Yun; Lee, Ping Yein; Ng, Chirk Jenn (Wiley Publishing Asia, 2015)
Patient decision-making role preference (DMRP) is a patient's preferred degree of control when making medical decisions. This descriptive qualitative study aimed to explore Malaysian patients' views on their DMRP. Between January 2011 and March 2012, 22 individual face-to-face in-depth interviews were conducted with patients with type 2 diabetes who were deciding about insulin initiation. The interviews were audio-recorded and analysed using a thematic approach. The age range of participants was 28–67 years old with 11 men. Ten patients preferred to make the decision themselves, six patients indicated that the clinician should make the decision and only one patient expressed a preference for a collaborative role. The following factors influenced DMRP: trust in clinicians, responsibility for diabetes care, level of knowledge and awareness, involvement of family and personal characteristics. In conclusion, the concept of shared decision-making is still alien, and a more participative communication style might help to facilitate patients' expression of DMRP.